Impact of oxygen on gallium doped germanium - N. Kuganathan; H. Bracht; K. Davazoglou; F. Kipke; A. Chroneos (AIP Advances, 2021)
Germanium (Ge) has advantageous materials properties and is considered as a mainstream material for nanoelectronic applications. Understanding dopant–defect interactions is important to form well-defined doped regions for devices. Gallium (Ga) is a key p-type dopant in Ge. In the present density functional theory study, we concentrate on the structures and electronic structures of Ga doped Ge in the presence of Ge vacancies and oxygen. We provide information on the defect structures and charge transfer between the doped Ga atom and the nearest neighbor Ge atom. The calculations show that the presence of Ga on the Ge site facilitates the formation of nearest neighbor Ge vacancies at 0.75 eV. The formation of interstitial oxygen is endoergic with the formation of −2 charge in both bulk Ge and Ga substituted Ge although the substitution of Ga has slightly less impact on the oxygen interstitial formation.